Organizing for Radical Innovation: Exploring Novel Insights. Issue 4 (2nd June 2017) - Colombo, Massimo G.; von Krogh, Georg; Rossi‐Lamastra, Cristina; Stephan, Paula E.
Abstract : While radical innovation brings extensive economic rewards to firms, it is an activity fraught with risk. Prior research has shown that such risks mainly stem from organizational arrangements (at the level of individuals, teams, firms, and inter firm collaborations), which are inadequate or inefficient to support radical innovation. The papers in this special issue on "Organizing for Radical Innovation: Exploring Novel Insights" take stock of past work and provide novel insights about how to organize for radical innovation. The overarching idea linking them is that radical innovation hinges on the creation of fundamentally new knowledge and the continuous stimulation of creativity. Thus, organizational arrangements that support such processes play a crucial role in explaining and predicting the successful commercialization of breakthrough ideas, radically new technologies, and solutions. In particular, the field of science, which in essence aims for the systematic production of new knowledge, can be a valid source of inspiration for how individuals, teams, firms, and interfirm collaborations should organize for radical innovation. Moving from these premises, in this introductory paper, we offer an overview of the topic of organizing for radical innovation and highlight possible linkages with the organizing principles. Then, we summarize the main insights from the papers in this special issue and use their core ideas to sketch a novel research agenda for scholars working at the intersection of organization theory, economics of science, and management of innovation.